The last refuge ([S.l.] Amphion Productions, 1994)
A documentary film on the history of Aetas of Zambales and their struggles for survival to save their ancestral land and vanishing culture.
VHS format.
Produced by Matthew Westfall and David Weissman ; written / directed by Matthew Westfall.
Narrated by Randy Oglesby.
Keywords: Aetas -- Social life and customs; Aetas -- Social conditions